Sustainable Livelihoods a Foundation for Rural Development Leads to Sustainability - Kumar, Abhijeet; Kumar, Avinash; Kumari, Swati; Kumari, Neha; Kumari, Sneha; Mishra, Puja (Problemy Ekorozwoju, 2023)
The primary objective of this study is to evaluate and analyse the significance of the Sustainable Livelihoods Approach (SLA) and its application to rural development projects and policies. A literature review is conducted, with the primary focus being on the primary components of the SLA. The researchers noted that the SLA effectively interrogates the livelihoods of the poor and the various mechanisms in the approach. These mechanisms include all forms of capital, the vulnerability aspect, livelihood strategies, and outcomes, as well as the different laws and regulations governing the access and use of resources. The research also noted that the SLA effectively addresses the poor’s vulnerabilities. Scholarly heavy hitters like Chambers and Scoones (1992) have pointed out that this method is all-encompassing and hierarchical. The methodology has demonstrated in a theoretical sense that it is beneficial in understanding the livelihoods problem of the less fortunate in rural communities. It is strongly suggested that the government and its development partners adopt and incorporate the SLA into their policies to ensure sustainable livelihoods leading to sustainable development.